Nonlinear Optical Thermometry—A Novel Temperature Sensing Strategy via Second Harmonic Generation (SHG) and Upconversion Luminescence in BaTiO3:Ho3+, Yb3+ Perovskite. Issue 12 (16th April 2021) - Zheng, Teng; Runowski, Marcin; Martín, Inocencio R.; Lis, Stefan; Vega, Mauricio; Llanos, Jaime
Abstract: Nonlinear optical spectroscopy may be a powerful tool for sensing of various intrinsic properties of materials and different state functions of the system. This is due to the strong dependence of nonlinear phenomena on numerous physicochemical factors. The feasibility of simultaneously employing the second harmonic generation (SHG) and upconversion luminescence (UCL) processes in BaTiO3 :Ho 3+, Yb 3+ for optical temperature sensing is demonstrated for the first time. Under 976 nm laser excitation, the evolution of the SHG and UCL band intensity ratio is correlated with temperature and calibrated within the temperature range of 25–305 °C. The band intensity ratio between SHG and UCL exhibits a sigmoidal dependence on temperature, and, hence, it can allow the detection of phase transitions from non‐centrosymmetric to centrosymmetric systems, and vice versa. Most importantly, from the perspective of optical temperature sensing, this work provides a novel and effective strategy for nonlinear optical thermometry, with high sensitivity of up to 2.78% °C –1 . Abstract : A novel strategy of nonlinear optical thermometry is presented for the first time. The temperature sensing concept is based on the nonlinear processes of second harmonic generation (SHG) and upconversion luminescence, observed in BaTiO3 perovskite particles. This highly sensitive method exploits a new and effective pathway for contactless temperature sensing, which is a promising alternative method to conventional fluorescence/luminescence intensity ratio (FIR/LIR) thermometry.